Artist’s Residency Award, Arts Residency Cairo, Egypt (1 month) - Stylianou-Lambert, Theopisti (My University, 2026)
Artist’s Residency Award, Arts Residency Cairo, Egypt (1 month)
Keywords: Arts and entertainment